MODEL PARTCIPATORY COMMUNICATION DALAM PEMBERDAYAAN KOMUNITAS PETANI - Yudhatama, Iranda (Jurnal Ilmu Komunikasi AKRAB, 2017)
AbstractIn the process of community empowerment there is a dimension of communication which is a way or method to disseminate and facilitate information or messages aimed at improving the quality of life of the community. One communication model in the context of community empowerment is a communication model of participatory communication based on community participation or beneficiaries, so that the empowerment messages can be effectively transformed through a partipatory dialogue model. Based on this context, this research tries to explore how communication model in the context of empowering peasant community in Nanggulan conducted by an association of Lumbung Tani which is a joint study between the facilitators of peasant empowerment (peasant activist) and peasant in relation to problems faced by peasants both in the context of policy and technical issues of cultivation. The results of this study show; (1) The facilitator plays a role as a partner for peasants to facilitate discussions and dialogues in every existing communication processs, (2) participatory and egalitarian nature that respects every vote or opinion of every individual involved in the process of engaging in Lumbung Tani; (3) pattern of communication built in Lumbung Tani, can be said as a participatory communication model.Key Words : Participatory Communication, Community Empowerment